The Fakara: a semi-arid agro-ecosystem under stress - Hiernaux, Pierre H.Y.; Ayantunde, Augustine A. (International Livestock Research Institute, 2004)
Besides the participation of the International Livestock Research Institute (ILRI) in the planning workshops and discussions that led to the writing up of the Desert Margins Program proposal, ILRI contribution to the first phase of the DMP-GEF program from July 2002 to June 2004 was centered on the development of methodologies to assess the natural resources of a Sahelian agro-ecosystem under stress, diagnosis of the status and trends of the productivity and the bio-diversity of the agro-ecosystem and performing preliminary tests of alternative management (DMP,2002). These activities are taking place in Fakara, a natural region, in an administrative district (canton) of western Niger, taking stock of the wealth of knowledge on the functioning of this semi-arid agro-ecosystem that resulted from a series of extensive studies carried out in this site from the 80’s onward. These studies were devoted to the soils, climate, hydrology, vegetation components, fauna, crops, livestock and farming systems of a small natural region of western Niger. This research background is summarized in the following introductory paragraphs. Then, the document reports more specifically on the research by International Livestock Research Institute in collaboration with the National Institute of Agriculture Research (INRAN), theInternational Crop Institutes for Semi-Arid Tropics (ICRISAT), and also with the regional Center AGRHYMET and ‘ Projet Intrants’, a rural development project developed by FAO and the Ministry of Agriculture Development of the Republic of Niger.